The role of economic integration in providing inter factors attractions to attract foreign direct investment- The experience of the European Union – - MEDJEDOUB, Bahoussi; Aries, Ammar (Milev Journal of Research and Studies, 2022)
The accession of the state to economic integration is necessary to provide factors to attract foreign direct investment as well as contemporary global economic changes, especially with regard to economic globalization. Today, the individual state cannot achieve what can be achieved when it joins the economic integration that enables it to activate foreign direct investment and achieve economical development. As most of the countries tended to establish alliances among themselves within the framework of economic integration in order to win the benefits it brings to them, including the provision of inter-attractions to attract foreign direct investment, which contribute to the raising of economic performance, this paper aims to present the experience of the European Union, Was a great success in the process of economic integration as it reached the monetary union and its increasing membership, which made it an economic force that competes with the world's strongest economies and its contribution to providing important inter-factors attractions to attract foreign direct investment and achieve greater development Economy.